Application of Quasi-Lagrangian Diagnostics and FGGE Data in a Study of East-Coast Cyclogenesis. - Roman,Donald A (1981)
This synoptic study of an explosive deepening event, the President's Day Storm of 17-20 February 1979, introduces and examines the Level III-b FGGE data in an oceanic storm. It applies the quantitative quasi-Lagrangian diagnostics techniques to both the FGGE data for a 48-hour period and a 24-hour LFM II prediction. Using a mass budget analysis in isobaric coordinates, the mass structure and circulation intensity are examined and intercomparisons between the FGGE observed cyclone and the LFM model predictions are made. Destabilization that is found during cyclogenesis is a maximum during the early time periods. The LFM fields did not develop the intensity, strength, or depth of circulation that is found in the observed FGGE data. This may be linked to a poor representation of the diabatic processes in the LFM model. (Author)